Designing of concrete pavement expansion joints based on climate conditions of Vietnam - Nguyen Hoang Long; Pham Cao Thang; Pham Duy Linh; Pham Tuan Anh; Pham Duc Phong; Pham Binh Thai (Journal of the Mechanical Behavior of Materials, 2019)
Main objective of this paper is to present ananalysis of necessity of providing expansion joints in the plain cement concrete pavement considering the climate and weather conditions of Vietnam. This study would help in the proper designing of expansion joints of highways and airport roads and thus can improve life span of cement concrete pavements to be constructed in Vietnam.